Sincronização de ciclos econômicos para as regiões brasileiras - Evangelista, Isaac Ricarte (2009)
INTRODUCTION: Developed countries are keen to know what "the current state of its economy", and tries to predict what should be the state in the near future. The government's interest in the subject is on the budget, social security, and even interventionist. Companies also are interested in the question, because it depends on the profitability of their business and their investments. Unfortunately, no current society has a direct estimate (and a predictor) of the "state of the economy", as this is a latent variable that is unobservable. Recently there is a greater concern in trying to measure the cyclical behavior of economies. In particular, the analysis of the business cycle synchronization between different countries becomes a subject of increasing interest in both academic and political circles. It is well to note that developed economies have become much more integrated in recent years. In these countries, trade flows have increased substantially and financial markets become more homogeneous. Thus, increasing attention is being devoted to examine whether efforts to coordinate their economic policies lead to greater synchronization of business cycles of these countries. It is expected that countries with strong links in terms of business cycle correlation face lower costs of joining a union than countries with less synchronized cyclic relativity. OBJECTIVES: In this context, the objectives of this study were to take a dating of recessions of economies of eight Brazilian states (Bahia, Minas Gerais, Pernambuco, Paraná, Rio de Janeiro, Rio Grande do Sul, Santa Catarina and São Paulo) determine if there is occurrence of synchronized business cycles between these local economies. METHODOLOGY: This way we used the monthly industrial production index number series (IPI) - General Industry from 1981: 01-2009: 03, released by the Brazilian Institute of Geography and Statistics (IBGE). Data were converted to quarterly by the arithmetic average total of 113 quarters. We use two different tools to obtain a dating business cycle for the economy of each Brazilian state. A non-parametric, given by Harding algorithm and Pagan (2002) and a parametric, through the Markov changes, following Hamilton (1989). Verification of the occurrence of synchronization of business cycles was made through the construction of a symmetric matrix of dissimilarity, as was proposed in Camacho's work (2005). RESULTS: we found that both methods of dating approached in order to try to present a dating to the recession in the economic cycle described by industry each state. As for synchronization verification of these cycles, both dissimilarity matrices suggest that the states of Minas Gerais, São Paulo, Santa Catarina and Rio Grande do Sul present synchronization of business cycles of their economies. The state of Rio de Janeiro is closer to the other states of the South and Southeast regions of representative states of the Northeast. The state of Paraná is not synchronized with the northeastern states, and there is a divergence of results of parametric and non-parametric arrays compared to other states in the south and southeast. The state of Bahia has an average synchronization, except with the states of Pernambuco and Paraná. Finally, Pernambuco seems to have a different dynamic in other states, so with portrays Carvalho (2005). CONCLUSION: Our results show a synchronization of business cycles between the states of the South and Southeast, with the exception of the state of Paraná. Pernambuco is not synchronized with any of the Brazilian states studied. The state of Bahia is closer to the South and Southeast, except Paraná and Rio de Janeiro, and as noted above, has no synchronization with the state of Pernambuco.